Myoinositol with Metformin and Myoinositol alone in infertile PCOS women undergoing ovulation induction cycles: A comparative study - Gade, Pramod; S, Aher Gautam; Sharmeen, Vazifdar (International Journal of Clinical and Biomedical Research, 2021)
Background: This was a prospective observational study conducted over a twelve-month duration in our institute to compare the combined effect of metformin and myoinositol with metformin alone. Method: A total of sixty patients were included in the study, and they were divided into two groups depending on whether they were given the combination or the single drug. Group A (n=30) was given Myoinositol 600 mg+Metformin 500 mg thrice a day, and Group B ( n=30) was given only Myoinositol 600 mg thrice a day. The outcome measure was clinical pregnancy rate and improvement in clinical and hormonal parameters after drug therapy. Results: BMI (p<0.01), modified Ferriman Gallaway score (p>0.05), and the was a significant improvement in the hormonal parameters (LH,FSH) in both the groups and the levels were found to be comparable after a period of 6 months. The clinical pregnancy rate after six cycles of ovulation was significantly higher in Group A as compared to Group B. In Group A, the total clinical pregnancy rate was 43.33%, and in Group B, it was 26.67%, respectively, and the end of 6 months and the difference was statistically significant (p = <0.01) Conclusion: Equal response in reduction of hormonal levels and clinical and laboratory parameters were seen in both groups, while better results in terms of clinical fertility rates were observed in the group that was given a combination of myoinositol with metformin.